2022
DOI: 10.1002/ejic.202200254
|View full text |Cite
|
Sign up to set email alerts
|

Migration Mechanism of the B−H Activation of Carboranes

Abstract: Density functional theory was used to investigate the possible migration mechanism of the BÀ H activation on carboranes. The effects of inducing groups, mediating atoms and ligands were clarified, and the specific reaction process and driving force of transition metal migration in carboranes were explored. The study of thermodynamics, dynamics, wave function analysis and bond order showed that hydrogen atoms and ligands had remarkable effects on metal migration in carboranes. Results indicated that the transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Thus, it is still necessary to explore new effective electrolyte systems to balance the ICE and the chemical stability. Although many researchers have tried to confirm the sodium and potassium storage mechanisms of the MX anodes, there are still controversies, and mainly focused on two viewpoints, which may be related to the design of the electrode materials and the influence of electrolyte. Taking the sodium storage mechanism of MoSe 2 as an example, one is that the initial state of MoSe 2 can be restored at full charging state after the insertion and conversion reaction, [159] and the other is that MoSe 2 cannot be fully recovered, in which Mo as the discharge product will not participate in the reaction, but Se and Na 2 Se are reacted in the subsequent cycles [194,195] . Moreover, with the assistance of DFT calculations, in situ Raman spectra and ex situ X‐ray absorption spectroscopy (XAS) analysis, Xu et al.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is still necessary to explore new effective electrolyte systems to balance the ICE and the chemical stability. Although many researchers have tried to confirm the sodium and potassium storage mechanisms of the MX anodes, there are still controversies, and mainly focused on two viewpoints, which may be related to the design of the electrode materials and the influence of electrolyte. Taking the sodium storage mechanism of MoSe 2 as an example, one is that the initial state of MoSe 2 can be restored at full charging state after the insertion and conversion reaction, [159] and the other is that MoSe 2 cannot be fully recovered, in which Mo as the discharge product will not participate in the reaction, but Se and Na 2 Se are reacted in the subsequent cycles [194,195] . Moreover, with the assistance of DFT calculations, in situ Raman spectra and ex situ X‐ray absorption spectroscopy (XAS) analysis, Xu et al.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Taking the sodium storage mechanism of MoSe 2 as an example, one is that the initial state of MoSe 2 can be restored at full charging state after the insertion and conversion reaction, [159] and the other is that MoSe 2 cannot be fully recovered, in which Mo as the discharge product will not participate in the reaction, but Se and Na 2 Se are reacted in the subsequent cycles. [194,195] Moreover, with the assistance of DFT calculations, in situ Raman spectra and ex situ X-ray absorption spectroscopy (XAS) analysis, Xu et al confirmed that the reversibility of the potassium storage of MoSe 2 depended on the electrode design. [196] Generally, the conversion process would cause serious structural dissociation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[27][28][29] Graphene can be used as the substrate and backbone for the growth of MoSe 2 , to support the entire structure containing other active materials. 30,31 Graphene can effectively inhibit the stacking problem and prevent the collapse and aggregation of active materials in the application process, thus, improving the electron and ion transfer rates. Among the graphene-based electrode materials, hierarchical nanostructures have attracted significant attention, as they synergistically enhance the advantages of graphene and nanoscale building blocks.…”
Section: Introductionmentioning
confidence: 99%